2008
DOI: 10.1093/jac/dkm512
|View full text |Cite
|
Sign up to set email alerts
|

Influences of dosage regimen and co-administration of low-molecular weight proteins and basic peptides on renal accumulation of arbekacin in mice

Abstract: These data may be useful for prevention of arbekacin-induced nephrotoxicity owing to reduction of renal accumulation of the aminoglycoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Because the average weight of used mouse is 27 g, and the average blood volume is 2 mL, the amount of lysozyme (0.57, 1.43, 2.86, or 5.72 μg per mouse) injected yielded a maximum concentration of 20, 50, 100, or 200 nM in the peripheral blood. Maximum amounts of used lysozyme (5.72 μg per mouse=212 μg/kg) administrated into mouse is safe because previous reports used up to 100 mg/kg [31], 300 mg/kg [32], or 1000 mg/kg [33]. To determine the molecular mechanism by which lysozyme inhibited the release of LPS-mediated HMGB1, we tested the effects of lysozyme on the transcriptional regulation of HMGB1 by LPS in HUVECs.…”
Section: Effect Of Lysozyme On Lps-and Clp-mediated Release Of Hmgb1mentioning
confidence: 99%
“…Because the average weight of used mouse is 27 g, and the average blood volume is 2 mL, the amount of lysozyme (0.57, 1.43, 2.86, or 5.72 μg per mouse) injected yielded a maximum concentration of 20, 50, 100, or 200 nM in the peripheral blood. Maximum amounts of used lysozyme (5.72 μg per mouse=212 μg/kg) administrated into mouse is safe because previous reports used up to 100 mg/kg [31], 300 mg/kg [32], or 1000 mg/kg [33]. To determine the molecular mechanism by which lysozyme inhibited the release of LPS-mediated HMGB1, we tested the effects of lysozyme on the transcriptional regulation of HMGB1 by LPS in HUVECs.…”
Section: Effect Of Lysozyme On Lps-and Clp-mediated Release Of Hmgb1mentioning
confidence: 99%
“…In a previous paper, we found that N-WASP181-200 had a 78-fold higher in vitro inhibitory potency for gentamicin binding to rat renal brush-border membrane than a low molecular weight protein, cytochrome c, when their IC 50 values were compared . However, the in vivo inhibitory potency of N-WASP181-200 was 16-fold as low as that of cytochrome c when their IC 50 values were compared . One of the main reasons for this disagreement between in vitro and in vivo studies was expected to be a poor delivery of N-WASP181-200 into the renal proximal tubule, where aminoglycosides are taken up.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, under in vivo conditions, the inhibitory effect of N-WASP181-200 on renal accumulation of aminoglycosides was much weaker than was expected from the in vitro inhibitory effect; the 50% inhibitory concentration (IC 50 ) value of N-WASP181-200 for gentamicin binding to renal brushborder membrane in vitro (0.041 mM) was much lower than that of cytochrome c (3.20 mM) (15), while its IC 50 value for renal arbekacin accumulation in vivo (19.6 µmol/kg) was found to be higher than that of cytochrome c (1.23 µmol/kg) (16). We speculated that one of the main reasons for the apparent inconsistency between in vitro and in vivo studies may be the rapid degradation in the plasma and/or extensive binding to various tissues after intravenous injection of N-WASP181-200.…”
Section: Introductionmentioning
confidence: 97%